A study of the internal security act 1960 (act 82) in Malaysia and its human rights implications in Malaysia / Luke Ressa Balang, Zaki Asyraf Zubir and Firdaus Azmir Md Nor - Balang, Luke Ressa; Zubir, Zaki Asyraf; Md Nor, Firdaus Azmir (2006)
In our project paper will focus on the Internal Security Act 1960(Act 82) and its effects in implementing the Human Rights in Malaysia. Basically, in our First Chapter we emphasizes on the problem statement, the objective of our study, literature review, and the provisional plan of the research. This has been done in our proposal before, what we present here is the edited and extra information which is relevant to our study. In Chapter two of our study, we discuss about the legislative setting and the aims of the Internal Security Act 1960. This will touch on the root of the Act, whereby the history of the ISA will be discussed in this chapter. Some jurisdictional issues would also be cited and critics in this chapter. The purpose of the ISA would be important in this chapter to understand the basic knowledge of the existence of the Internal Security Act 1960. Under Chapter three the critique of the use of Internal Security Act in Apostasy will be emphasized. With the references of Quran and Hadith, and some apostasy cases, we will determine the effect of ISA in handling this matter of Apostasy. Chapter Four, would be the last chapter on conclusions and recommendations. Some recommendations would be reference from the Independent body on what should be amended in the provisions of Internal Security Act. The Amnesty International, SUHAKAM, would be the best reference for us to analyze the weaknesses and challenges of ISA in Malaysia.